Mapping of T Cell Subsets in the Tumor Microenvironment of Multiple Myeloma and its Precursor Conditions - Steinar Bragi Gunnarsson 1998- (2023)
The bone marrow tumor microenvironment (BMME) in multiple myeloma (MM) is essential for maintaining anti-tumor activity. Dysregulation of normal immune responses is believed to be an important factor in tumor evasion and a contributing factor in the development of active MM from its precursor conditions, monoclonal gammopathy of undetermined significance (MGUS) and smoldering multiple myeloma (SMM). T cells are key immune regulators and are essential for maintain effective anti-tumor activity with their cytotoxicity and suppressor abilities. However, with those cells being altered and dysfunctional in MM it has been documented that they suppress the immune system more than the disease itself, allowing clonal plasma cells to keep growing and surviving. The aim of this study was to map T cell subsets in the BMME in a screened population of all stages of MM development. Participants were recruited from the Iceland Screens, Treats, or Prevents MM (iStopMM) study, a population-based screening study (N = 80,759) for MM precursors and randomized trial-follow strategies. BM aspirate samples from individuals with MM and its precursors conditions were analyzed using multiparameter flow cytometry (MFC) and automatic clustering used to quantify T cell subsets, notably, CD4+, CD8+, regulatory (Tregs), and TCRγδ T cells, along with the respective maturation stages of CD4+ and CD8+ T cells: naïve, effector memory (EM), central memory (CM), terminally differentiated effector memory (Temra). The distribution of T cell subsets was compared between disease stages and according to the presence of the independent risk factor for progression of MGUS and SMM to active MM, 95% or more of clonal plasma cells within the plasma cell compartment in BM. A total of 138 individuals were included in the study cohort (40 had MGUS, 78 had SMM and 20 had MM). The percentage of total T cell was found to be significantly higher in individuals with SMM and MM when compared to MGUS (p = 0.003 for MGUS vs SMM and p = 0.013 for MGUS vs MM). The highest ...